(untitled) (Revista Brasileira Multidisciplinar, 2024)
Natural gums, such as gellan and carrageenan gum, are used in pharmaceutical formulations for their thickening, stabilizing, and gelling action. Thus, the aim of the work was to prepare semisolid emulsions based on natural gums to incorporate chamomile oil, with the aim of using them for skin disorders. The formulations were prepared from the emulsion between an oily phase, composed of cetostearyl alcohol, ethoxylated cetostearyl alcohol, vitamin E, and chamomile oil, and an aqueous phase containing propylene glycol, gellan (F1) or carrageenan gum (F2), EDTA, preservative and water. The formulations were evaluated in relation to their pH, density, spreadability, rheological test, infrared analysis, and centrifugation test. The pH remained in the acidic range, being 5.05 ± 0.05 for F1 and 4.77 ± 0.26 for F2. The density remained within the range recommended by ANVISA for both formulations. In the spreadability test, there was an increase in the spread area as the weight was applied, with F2 (12.65 ± 1.02 mm2/g) appearing to have a better spreading capacity than F1 (10.25 ± 1.5 mm2/g). The formulations behaved like non-Newtonian fluids with viscoelastic characteristics. Infrared analysis showed similarities between the formulations, highlighting stretching bands around 3500 cm-1 related to hydroxyls in the gums. In the centrifugation test, F2 showed phase separation, suggesting instability. The emulsions based on natural gums showed that gellan gum had better characteristics and stability compared to carrageenan gum, being more promising for application to the skin.